Biophysical and pharmacological characterization of a full-length synthetic analog of the antitumor polypeptide crotamine - de Carvalho Porta, Lucas; Fadel, Valmir [UNESP]; D’Arc Campeiro, Joana; Oliveira, Eduardo Brandt; Godinho, Rosely Oliveira; Hayashi, Mirian Akemi Furuie (Springer Nature, 2020)
Abstract: Crotamine is a polypeptide isolated from the venom of a South American rattlesnake. Among the properties and biological activities of crotamine, the most extraordinary is its ability to enter cells with unique selective affinity and cytotoxic activity against actively proliferating cells, such as tumor cells. This peptide is also a cargo carrier, and anticipating commercial application of this native polypeptide as a potential theranostic compound against cancer, we performed here a side-by-side characterization of a chemically synthesized full-length crotamine compared with its native counterpart. The structural, biophysical, and pharmacological properties were evaluated. Comparative NMR studies showed structural conservation of synthetic crotamine. Moreover, similarly to native crotamine, the synthetic polypeptide was also capable of inhibiting tumor growth in vivo, increasing the survival of mice bearing subcutaneous tumor. We also confirmed the ability of synthetic crotamine to transfect and transport DNA into eukaryotic cells, in addition to the importance of proteoglycans on cell surface for its internalization. This work opens new opportunities for future evaluation of chimeric and/or point-mutated analogs of this snake polypeptide, aiming for improving crotamine properties and applications, as well as possibly diminishing its potential toxic effects. Key messages: • Synthetic crotamine showed ex vivo and in vivo activities similar to native peptide. • Synthetic crotamine structure conservation was demonstrated by NMR analysis. • Synthetic crotamine is able to transfect and transport DNA into eukaryotic cells. • Synthetic crotamine shows tumor growth inhibition in vivo. • Synthetic crotamine increases survival of mice bearing tumor.
Keywords: CPP; Crotamine; Hind limb paralysis; Melanoma tumor; Proteoglycans; Skeletal muscle contraction; Structural NMR